2022
DOI: 10.1155/2022/5183562
|View full text |Cite
|
Sign up to set email alerts
|

Antidesma thwaitesianum Müll. Arg. Fruit Juice, Its Phytochemical Contents, Antimicrobial Activity, and Application in Chiffon Cake

Abstract: Antidesma thwaitesianum Müll. Arg. or Mao is well-known in Thailand for its use in soft drinks and wine. This study investigated the potential of its fruit juice as a food preservative based on its antimicrobial activity against food-borne pathogens and spoilage. The fruit juice had antibacterial activity against Bacillus cereus TISTR1527, Staphylococcus aureus TISTR2329, Listeria monocytogenes DMST17303, Pseudomonas aeruginosa TISTR357, Salmonella Typhimurium DMST562, and Escherichia coli TISTR074. The minimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…8 The utilization of mamao fruit in Thailand is processed to several product including soft drink, alcoholic beverages, as well as functional foods, and this finding was supported to its products from previous studies. 12 Fruit juice is a preserving juice product by decreasing water activity for prevention of its spoilage by inhibition of microbial growth and extending the product's shelf life. Generally, the quality of juice is depended on physical appearance and taste sensing.…”
Section: Resultsmentioning
confidence: 99%
“…8 The utilization of mamao fruit in Thailand is processed to several product including soft drink, alcoholic beverages, as well as functional foods, and this finding was supported to its products from previous studies. 12 Fruit juice is a preserving juice product by decreasing water activity for prevention of its spoilage by inhibition of microbial growth and extending the product's shelf life. Generally, the quality of juice is depended on physical appearance and taste sensing.…”
Section: Resultsmentioning
confidence: 99%
“…11,56 A. thwaitesianum juice had radical scavenging activity against both DPPH radicals with EC 50 value of 72.18 μg/ml and ABTS + radicals with EC 50 value of 76.95 μg/ml. The FRAP value was 184.59 mg Fe 2+/ g. 65…”
Section: Pharmacological Studiesmentioning
confidence: 94%
“…11,56 A. thwaitesianum juice had radical scavenging activity against both DPPH radicals with EC 50 value of 72.18 μg/ml and ABTS + radicals with EC 50 value of 76.95 μg/ml. The FRAP value was 184.59 mg Fe 2+/ g. 65 The anti-oxidant activities are usually believed to correlate with total phenolic or flavonoid compounds. However, the study by Jorjong's group indicated that there was no correlation between anti-oxidant capacity and total flavonoid, implying that flavonoids might not be mainly responsible compound class for anti-oxidant effects.…”
Section: Anti-oxidant Activitymentioning
confidence: 98%
See 2 more Smart Citations